Hydroperoxy fatty acid cycling mediated by mitochondrial uncoupling protein UCP2 - Jaburek, Martin; Miyamoto, Sayuri; Di Mascio, Paolo; Garlid, Keith D; Jezek, Petr (The Journal of biological chemistry, 2004)
Functional activation of mitochondrial uncoupling protein-2 (UCP2) is proposed to decrease reactive oxygen species production. Skulachev and Goglia (Skulachev, V. P., and Goglia, F. (2003) FASEB J. 17, 1585-1591) hypothesized that hydroperoxy fatty acid anions are translocated by UCPs but cannot flip-flop across the membrane. We found that the second aspect is otherwise; the addition of synthesized linoleic acid hydroperoxides (LAOOH, a mix of four isomers) caused a fast flip-flop-dependent acidification of liposomes, comparable with the linoleic acid (LA)-dependent acidification. Using Escherichia coli-expressed UCP2 reconstituted into liposomes we found that LAOOH induced purine nucleotide-sensitive H(+) uniport in UCP2-proteoliposomes with higher affinity than LA (K(m) values 97 microM for LAOOH and 275 microM for LA). In UCP2-proteoliposomes LAOOH also induced purine nucleotide-sensitive K(+) influx balanced by anionic charge transfer, indicating that LAOOH was also transported as an anion with higher affinity than linoleate anion, the K(m) values being 90 and 350 microM, respectively. These data suggest that hydroperoxy fatty acids are transported via UCP2 by a fatty acid cycling mechanism. This may alternatively explain the observed activation of UCP2 by the externally generated superoxide. The ability of LAOOH to induce UCP2-mediated H(+) uniport points to the essential role of superoxide reaction products, such as hydroperoxyl radical, hydroxyl radical, or peroxynitrite, initiating lipoperoxidation, the released products of which support the UCP2-mediated uncoupling and promote the feedback down-regulation of mitochondrial reactive oxygen species production.
Keywords: Purines; down regulace; anionty; Mitochondria; Potassium; Plasmids; hydroxylový radikál; draslík; Hydroxyl Radical; Liposomes; reaktivní formy kyslíku; Models, Chemical; mastné kyseliny; membránové transportní proteiny; komplementární DNA; Lipid Peroxides; Peroxynitrous Acid; puriny; iontové kanály; Escherichia coli; kyselina peroxydusitá; Uncoupling Protein 2; Fatty Acids; Models, Biological; mitochondriální proteiny; protony; Membrane Transport Proteins; liposomy; Ion Channels; Mitochondrial Proteins; Reactive Oxygen Species; Time Factors; Cell Membrane; lipidové peroxidy; kinetika; Down-Regulation; lidé; biologické modely; Humans; Protons; buněčná membrána; časové faktory; Linoleic Acid; plazmidy; Anions; Protein Transport; Linoleic Acids; DNA, Complementary; kyselina linolová; chemické modely; transport proteinů; Kinetics; uncoupling protein 2; mitochondrie; kyseliny linolové